PELATIHAN PENERAPAN SISTEM INFORMASI PENDIDIKAN UNTUK PENGOLAHAN DATA GURU PADA MA AL – FALAH PALEMBANG: PELATIHAN PENERAPAN SISTEM INFORMASI PENDIDIKAN UNTUK PENGOLAHAN DATA GURU PADA MA AL – FALAH PALEMBANG - Sayuti, Akmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Effective and efficient teacher data management is an important aspect in supporting education management at Madrasah Aliyah (MA). In this context, MA Al-Falah Palembang faces challenges in managing teacher data manually which often causes delays, data errors, and less than optimal data-based decision making. Therefore, training on the application of educational information systems was held as a solution to increase the efficiency and accuracy of teacher data management. The aim of this training is to provide knowledge and skills to administrative staff and education personnel at MA Al-Falah in using technology-based educational information systems for processing teacher data. The methods used include presentations, live demonstrations, and practical sessions with information systems that have been designed according to needs. The results of the training showed an increase in participants' understanding and ability to operate educational information systems. Apart from that, the information system implemented has been proven to be able to simplify the process of processing teacher data, such as managing personal data, teaching schedules and performance assessments. As a result, school management can focus more on improving the overall quality of education. With this training, it is hoped that MA Al-Falah Palembang can continue to optimize the use of technology in education management, so as to achieve work efficiency and improve the quality of service to teachers and students.